Implementasi Teknik SEO On-Page dan Off-Page dalam Meningkatkan Peringkat Website Klien PT. Deus Code (Studi Kasus greenmile.co.id) - Pradana, Melkisedek Luky Rosano Adi; Prihati, Yani; Prakoso, Satrio Agung (STMIK Banjarbaru, 2024)
In the digital era, SEO strategies were essential to securing high rankings in search results. This study integrated internal optimizations (SEO On-Page) such as title tags, meta descriptions, and page speed, along with external efforts (SEO Off-Page) including quality backlink building and social media signals. The case study utilized data from periods before and after the implementation of these SEO strategies. The results demonstrated significant improvements in user numbers, average interaction duration, and a reduction in bounce rate. The website 's ranking improved from unlisted to the third page of Google's SERP for the keyword